2022
DOI: 10.3390/gels8100611
|View full text |Cite
|
Sign up to set email alerts
|

Bioprinting of 3D Adipose Tissue Models Using a GelMA-Bioink with Human Mature Adipocytes or Human Adipose-Derived Stem Cells

Abstract: Adipose tissue is related to the development and manifestation of multiple diseases, demonstrating the importance of suitable in vitro models for research purposes. In this study, adipose tissue lobuli were explanted, cultured, and used as an adipose tissue control to evaluate in vitro generated adipose tissue models. During culture, lobule exhibited a stable weight, lactate dehydrogenase, and glycerol release over 15 days. For building up in vitro adipose tissue models, we adapted the biomaterial gelatin meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“…54 In other reports, humanderived stem cells encapsulated in gellan gum were also differentiated into mature adipocytes. 55,56 In other words, when these data and our findings are combined, it is concluded that these anionic polymers can be more favorable for the culture of mature adipocytes without functional change or for adipocyte differentiation of precursor cells, rather than dedifferentiation.…”
Section: Papersupporting
confidence: 54%
See 1 more Smart Citation
“…54 In other reports, humanderived stem cells encapsulated in gellan gum were also differentiated into mature adipocytes. 55,56 In other words, when these data and our findings are combined, it is concluded that these anionic polymers can be more favorable for the culture of mature adipocytes without functional change or for adipocyte differentiation of precursor cells, rather than dedifferentiation.…”
Section: Papersupporting
confidence: 54%
“…Biomaterials Science in various studies that they can actually be used for preserving mature adipocyte function instead or even for differentiating preadipocytes into adipocytes. 54,55 In relation to this matter, we noticed that fully developed fat cells predominantly retained their rounded morphology when subjected to ceiling culture for seven days on surfaces coated with gelatin and gellan gum (Fig. S7 †).…”
Section: Papermentioning
confidence: 90%
“…[ 46 ] As a consequence, large nozzle diameters and low pressure are needed for gentle printing conditions in this context. [ 47 ] This is, however, associated with low resolution and prolonged fabrication times, which in turn may also be harmful for the processed cells. VBP as a layer‐less and nozzle‐free biofabrication platform represents an attractive method for the manufacturing of constructs containing fragile cells, furthermore the fast fabrication speed could benefit the cell survival.…”
Section: Resultsmentioning
confidence: 99%
“…Gelatin in the form of methacryloylated gelatin (GelMA) is widely used in tissue engineering, particularly in the generation of bone, cartilage, skin, and vascular networks. 65,66 GelMA is a modied gel with photosensitive functional groups introduced into the gelatin side chain, 67,68 which retains the good biocompatibility and degradation properties of gelatin, forms covalent cross-linked hydrogels with good thermal stability under the action of UV light and photo-initiators, and shows good printing adaptability and biocompatibility in the eld of 3D bioprinting. 69,70 However, it is difficult to form biological scaffolds by extrusion 3D printing due to the poor mechanical properties and structural maintenance of GelMA crosslinked by light.…”
Section: Gelatinmentioning
confidence: 99%